Qingyang sachet in Gansu province: A Preliminary Investigation on Sustainable Development of Local Traditional Handicraft - Zheng , Di; Ke, Yihan (Journal of Ecohumanism, 2025)
As a local traditional handicraft, Qingyang sachet in Gansu province not only carries a strong local cultural heritage, but also an important part of China’s intangible cultural heritage. However, under the impact of modernization and globalization, its inheritance and development face many challenges. Using Creswell’s nine-key step framework for qualitative data analysis, a study on Qingyang sachets in Gansu Province, China, identified four research questions through ethnography, literature studies, IPAR methodology, in-depth interviews, observations, and group discussions. Local Qingyang volunteers participated as discussants, interviewers, and observers for target groups including government officials, workers, artisans, managers, and designers. The study found that Qingyang sachets, also known as "Chu Chu," are a folk custom reflecting the simplicity, health, and positivity of the laboring people, embodying the broad and profound spirit of ancient Chinese civilization. These sachets, with strong traditional senses and exquisite handmade work, are treasures of folk art that include embroidery, dyeing, and other craft processes. The handmade silk pouches, stuffed with Chinese herbal medicines and embroidered with colorful patterns, symbolize optimism, good luck, and the avoidance of evil. The research aims to provide ideas for the sustainable development of traditional handicrafts and provide reference for the protection and inheritance of other intangible cultural heritage projects.